International multicenter survey on screening and confirmatory testing in primary aldosteronism. Issue 1 (13th January 2023) - Naruse, Mitsuhide; Murakami, Masanori; Katabami, Takuyuki; Kocjan, Tomaz; Parasiliti-Caprino, Mirko; Quinkler, Marcus; St-Jean, Matthieu; O'Toole, Sam; Ceccato, Filippo; Kraljevic, Ivana; Kastelan, Darko; Tsuiki, Mika; et al.
Abstract: Objective: Primary aldosteronism (PA) is one of the most frequent causes of secondary hypertension. Although clinical practice guidelines recommend a diagnostic process, details of the steps remain incompletely standardized. Design: In the present SCOT-PA survey, we have investigated the diversity of approaches utilized for each diagnostic step in different expert centers through a survey using Google questionnaires. A total of 33 centers from 3 continents participated. Results: We demonstrated a prominent diversity in the conditions of blood sampling, assay methods for aldosterone and renin, and the methods and diagnostic cutoff for screening and confirmatory tests. The most standard measures were modification of antihypertensive medication and sitting posture for blood sampling, measurement of plasma aldosterone concentration (PAC) and active renin concentration by chemiluminescence enzyme immunoassay, a combination of aldosterone-to-renin ratio with PAC as an index for screening, and saline infusion test in a seated position for confirmatory testing. The cutoff values for screening and confirmatory testing showed significant variation among centers. Conclusions: Diversity of the diagnostic steps may lead to an inconsistent diagnosis of PA among centers and limit comparison of evidence for PA between different centers. We expect the impact of this diversity to be most prominent in patients with mild PA. The survey raises 2 issues: the need for standardization of the diagnostic process and revisiting the concept of mild PA. Further standardization of the diagnostic process/criteria will improve the quality of evidence and management of patients with PA.